THE NEED FOR THE IMPLEMENTATION OF PASCO DIGITAL LABORATORIES, WHICH PROVIDES THE POSSIBILITY OF DIGITIZATION OF STEAM SCIENCES - Sh. R.Turdiyev (American Journals, 2023)
This article talks about the possibility of launching digital laboratories such as PASCO in IT incubation centers of higher education institutions and using them for educational processes, as well as some of its advantages.
Keywords: STEAM science, PASCO, Higher education, digital laboratory, creative thinking, IT center, STEAM approach, STEAM education.